Engineering geological properties of residual soil (along Doi Suthep Hill, Chiang Mai) - Shrestha, Jeevn Lal; Prinya Nutalaya; Yudhbir; Prinzl, Frediric (Bangkok : Asian Institute of Technology, 1982)
The physical, mineralogical and engineering properties of a granite-gneiss residual soil at Doi Suthep Hill, Chiang Mai, Northern Thailand, are investigated. A detailed field study was carried out and the soil profiles were described in the field. Field tests such as pocket penetrometer, hand cone penetrometer, field density and field permeability tests were also carried out. The disturbed and undisturbed box samples were taken. Apart from this the model analysis of sand fraction, petrography of whole soil and x-ray diffraction analysis of clay fraction were studied for the mineralogical properties. Also the direct shear tests and consolidation tests were performed. From the results it shows that the completely weathered granite of weathering grade V (according to MOYE's classification system) is a weak zone. It lies below 2.5 to 4.0 m. from the surface. The thickness of this zone varies from 4.0 to 7.0 m Above this zone there is a zone of granitic soil of weathering grade VI in which the cohesion intercept is 5.4 t./sq. m. and the angle of shearing resistance is 56.30. This zone contains high amount of clay (<0.002 mm.)ranging from 20.5 to 42.0 % and plasticity index ranging from 28 to 40.3. The activity of the clay in this zone is normal to inactive due to the high amount of kaolinite. The specific gravity values range from 2.62 to 2.64 and the dry density from 1.41 to 1.75 t./cu. m.. The field permeability of this zone ranges from 4.60x10-4 to 2.80x10-52 cm./sec. This zone has a less amount of weathered materials like sericite, chlorite due to the transformation of these materials into clays. Also a high amount (24.3%) of iron oxide is present. The weak zone of completely weathered granite of weathering grade V is more sandy. The clay content of this zone ranges from 5.0 to 14.8 % It is of non-plastic nature due to the high amount of kaolinite (about 90 to 95%) present in it. The specific gravity values ranges from 2.60 to 2.64 and the dry density values from 1.49 to 1.60 t./cu. m.. This zone is very friable in nature. The horizontal shear resistance ranges from 1.5 to 4.5 kg./sq. cm. whereas the cone resistance ranges from 5.25 to 9.17 kg./sq. com.. The residual angle of shearing resistance and cohesion are 36.5 and 1.7 t./sq. m. respectively. The field permeability of this zone is 8.28x10-4 to 9.80x10-4 cm./sec.. The amount of sericite increases in this zone and the clay material and iron oxide decrease slightly. In the highly weathered zone of grade IV, below the weak zone the clay content decreases and it ranges between 2.5 to 10.8 %. The amount of quartz, plagioclase, biotite and iron oxide increases slightly. The amount of clay decreases to 6.8 %. The clay is mainly kaolinite. The specific gravity values ranges from 2.62 to 2.65 and the dry density values from 1.58 to 1.91 t./cu. m.. This zone has a high angle of horizontal shear resistance and cone resistance. The residual angle of shearing resistance and cohesion are 42 a̕nd 0.62 t./sq. m. respectively. The field permeability of this zone is 1.72x10-3 to 7.06x10-4 cm./sec.. The model analysis of the fresh to slightly weathered rock is also carried out. The result shows that some of the grains of plagioclase, K-feldspar and biotite are weathered. The results also show that oven drying reduces the liquid limit and plastic limit values. In most cases the clay fraction (<0.002 mm.) reduces due to air and oven drying. Significant change is observed in oven during the granitic soil of weathering grade VI (1.9 to 16.2 %). In air drying only a sight change is observed. For the lower weathering grade the change in clay content is not so significant (2.0 to 5.0 % only). By oven drying significant change is also observed in liquid limit (4.1 to 14.1 %) and plasticity index (0.5 to 14.7) in the grade VI granitic soil. The plastic limit changes slightly and the activity decreases slightly.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Engineering and Technology
Thesis (M. Sc.) - Asian Institute of Technology, 1982
Keywords: Soil mechanics -- Thailand -- Doi Suthep Hill